2022
DOI: 10.1039/d2bm01281b
|View full text |Cite
|
Sign up to set email alerts
|

Combined phototherapy with metabolic reprogramming-targeted albumin nanoparticles for treating breast cancer

Abstract: Triple-negative breast cancer (TNBC) is characterized by rapid tumor growth and resistance to cancer therapy and has a poor prognosis. Accumulating data has revealed that cancer metabolism relies on both...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…27 In TNBC, albumin nanoparticles have been used for delivering multiple therapeutics ranging from irinotecan, 28 a curcumin derivative, 29 to olaparib 30 to phototherapeutic agents. 31 Endocytosis of albumin by different types of cells may follow different but distinct mechanisms. Albumin uptake happens by clathrin-mediated endocytosis in renal proximal cells and alveolar type II cells, whereas cultured astrocytes, endothelial cells, and hepatocytes make use of caveolaemediated endocytosis to facilitate albumin entry inside the cells.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…27 In TNBC, albumin nanoparticles have been used for delivering multiple therapeutics ranging from irinotecan, 28 a curcumin derivative, 29 to olaparib 30 to phototherapeutic agents. 31 Endocytosis of albumin by different types of cells may follow different but distinct mechanisms. Albumin uptake happens by clathrin-mediated endocytosis in renal proximal cells and alveolar type II cells, whereas cultured astrocytes, endothelial cells, and hepatocytes make use of caveolaemediated endocytosis to facilitate albumin entry inside the cells.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Albumin has also been shown to accumulate within the tumor site owing to several factors like leaky capillary action and defective lymphatic drainage within the tumor surroundings, transcytosis of albumin upon binding to the endothelial gp60 receptor and also tumor-overexpressed SPARC receptor, and last, increased uptake by growing tumor cells as a source of amino acids and energy . In TNBC, albumin nanoparticles have been used for delivering multiple therapeutics ranging from irinotecan, a curcumin derivative, to olaparib to phototherapeutic agents . Endocytosis of albumin by different types of cells may follow different but distinct mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…The following in vivo investigations showed that combined glycolysis inhibition and photodynamic therapy (PDT) was more powerful than single treatment in inhibiting the tumour growth. 110 Zhuang and co-workers designed Prussian Blue NPs coated with molecularly imprinted polymers. By using HK epitopes as the template for molecularly imprinting, these NPs could effectively bind to HK and further restrict glycolysis.…”
Section: Metabolism-targeted Nanomedicine For Cancer Therapymentioning
confidence: 99%
“…Furthermore, tumor cell metabolism can be reprogrammed to amplify PDTinduced ICD, promote dendritic cell (DC) maturation, and inhibit tumor proliferation. [59,[105][106][107][108][109] This section will focus on the strategies closely related to PDT treatment in recent years, mainly aerobic glycolysis, OXPHOS, glutamine, and cholesterol metabolism intervention strategies to amplify PDT. A more comprehensive strategies summary is shown in Table 2.…”
Section: Intervention Of Tumor Cell Metabolismmentioning
confidence: 99%
“…[48,56] These complex factors shaped the tumor rich in hydrogen peroxide (H 2 O 2 ), glutathione (GSH), and acidic conditions (low pH), as well as hypoxia environment characteristics. [57][58][59] More significantly, the infiltrating immunosuppressive-related cells in TME and the molecules they express affect tumor immune response. In particular, immune checkpoints represented by programmed death factor 1 (PD-1) and its ligand (PD-L1) and Indoleamine 2,3dioxygenase (IDO) are the most concerned tumor immune escape mechanisms in recent years.…”
Section: Introductionmentioning
confidence: 99%